MEMETAKAN PERILAKU ANAK DALAM MENGONSUMSI MEDIA SEBAGAI UPAYA PENGEMBANGAN PROGRAM “MAGELANG KOTA LAYAK ANAK” - Lintang Citra Christiani; Jaduk Gilang Pembayun (Jurnal Komunikasi dan Kajian Media, 2022)
Kota Layak Anak (KLA) is a government program that is being developed, one of which is in the Magelang city which received appreciation as the KLA category Nindya. However, this program has not included the criteria for media literacy as one indicator of its success. Meanwhile children dependent on the media. Research conducted by this survey method seeks to map patterns of child media behavior as a baseline data for the development of KLA policy and the basis for the media literacy movement. The results show that children in the Magelang city prefer to choose a combination of television and internet media to meet their needs. Parents provide access to media, but do not provide guidance to children when consuming media. At the same time, the government and schools are doing policy centered in media literacy that are not effective in their implementation. On the other hand, local wisdom in the form of the religious values of the Magelang community can reduce the negative impact of the media on children.